GTM VS TPR: UNVEILING VOCABULARY TEACHING METHODS ON THE 'JAGO BAHASA' YOUTUBE CHANNEL - Juliasti, Linda Saufi; Jannah, Miftahul; Assapari, Muhammad Mugni; Agustina, Titik (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to examine the implementation of the Grammar Translation Method (GTM) and the Total Physical Response (TPR) method by English tutors on the JAGO BAHASA YouTube channel and evaluate their effectiveness in teaching English vocabulary. The research uses a descriptive qualitative approach with a case study design to deeply understand the specific context and practices in an educational setting. The analysis focuses on 15 short videos (20-60 seconds each) from up to 12 tutors, starting from January to early March 2024. The results show that the use of GTM and TPR on the YouTube channel has both positive and negative impacts on English vocabulary learning. Overall, the analysis demonstrates that the tutors combine both methods, providing a comprehensive learning experience that caters to various learning styles and enhances the effectiveness of vocabulary instruction. Furthermore, the findings demonstrate that the Grammar-Translation Method and the TPR method are effective in enhancing vocabulary learning, resulting in a well-rounded and engaging language learning experience.